A novel BODIPY-based MOF photocatalyst for efficient visible-light-driven hydrogen evolution. Issue 17 (8th April 2019) - Yang, Heng; Wang, Jinming; Ma, Ji; Yang, Hong; Zhang, Jing; Lv, Kangle; Wen, Lili; Peng, Tianyou
Abstract : The first BODIPY-based MOF decorated with a Pt co-catalyst exhibited efficient photocatalytic H2 evolution under visible-light illumination, representing the most visible-light photoactive MOF material for H2 evolution from water thus far. Abstract : Considerable attention has been paid to promising applications of photoactive metal–organic frameworks (MOFs) in visible-light-enhanced hydrogen production. In this study, a pillared-paddlewheel type metal–organic framework [Zn2 (BODIPY)(BPDC)2 ]·H2 O (denoted as CCNU-1) featuring BODIPY struts, and capable of efficiently absorbing visible light from 200 to 800 nm, has been fabricated, which is thought to be the first BODIPY-based MOF decorated with Pt nanoparticles as the co-catalyst for efficient photocatalytic H2 generation under visible-light illumination. Impressively, Pt/CCNU-1 exhibited a remarkable H2 production rate as high as 4680 μmol g −1 h −1 with the use ofl -ascorbic acid as a sacrificial reagent from an aqueous medium, and a high apparent quantum efficiency of 9.06% at 420 nm. To our knowledge, Pt/CCNU-1 is the most visible-light photoactive Pt/MOF composite for H2 generation from water hitherto, highlighting the promising future of MOF materials in solar-to-chemical energy conversion. This work provides significant insights into the development of MOF-based systems for visible-light-responsive photocatalysts for water reduction.